Emigration and Economic Crisis: Recent Evidence from Uruguay - Adela Pellegrino; Andrea Vigorito (El Colegio de la Frontera Norte, A.C., 2005)
Uruguay is one of the South American countries with a significant proportion of population living abroad. Since the 1970s, it has had net emigration. Although this trend weakened considerably in the early 1990s, the momentum was regained with the advent of a severe economic crisis in 1999. This article discusses the characteristics of recent Uruguayan emigration, and it provides evidence of the relationship between economic crisis and emigration. The volume of population outflow in 2002 was comparable to the waves of emigration that took place in the 1970s. College-educated emigrants are overrepresented when compared to the general population. Having access to networks of Uruguayan emigrants in destination countries correlates with the probability that a household had a member who emigrated in 2002.